Consumo perjudicial del alcohol como factor de riesgo para cáncer gástrico - García García, Luis Oswaldo (2017)
Background: Gastric cancer (GC) is the second most common cause of cancer death in the world and unfortunately most cases are detected in advanced states. Epidemiological findings on alcohol consumption in relation to gastric cancer remain controversial. The objetive of this study was to examine the effect of alcohol consumption on the risk of gastric cancer. Methods: An observational, analytical study was carried out to compare proportions with respect to the harmful consumption of alcohol related to gastric cancer (CG): one with CG (cases) and others without CG (controls) treated at Regional Hospitals Bethlehem of Trujillo. The statistical test for Chi-square was used to estimate the degree of association of risk ODDS RATIO and their confidence intervals to 95% of significant risk factor. Results: A positive association was found regarding harmful alcohol consumption and the risk of developing gastric cancer (OR: 2.12 CI 95% of 1.19- 3.78). The average age of the cases was 63.1 years for women and 62.43 years for men. The proportion of harmful alcohol consumption in gastric cancer patients was 63.07% Conclusions: This study supports a link between alcohol consumption (mainly ethanol) and the development of gastric cancer in the population of Trujillo